Shariah issues in the application of repurchase undertaking in sukuk mudarabah - Mohd Sadad, Mahmud; Ahmad Shukri, Yazid; Ibraheem Alani, Abdul Kareem (2020)
The Malaysia Sukuk market has grown quickly over the past two decades which makes it an integral part of the Malaysia capital market. It keeps embracing innovative structure, as underlined by the dispatch of Sukuk utilizing the ideas such as ijarah, salam, musharakah and mudarabah. The higher level of dynamism in the market is reflected by the growth of sophisticated Sukuk arrangements that are now structured-based on numerous Shariah ideas to meet the needs of the customer (Sukuk holders). Owing to the foregoing, the objective of this paper is to show that there are few Shariah issues which require further discussion to guarantee compliance with Shariah (Islamic law). This paper discusses Shariah issues in Sukuk mudarabah and focuses on the application of repurchase undertaking in Sukuk mudarabah structure using Malaysia as a case study. The methodology applied for this study is based on previous studies and literature related to the topic which were gathered from different published articles, reports and several sources. This paper recommends that Shariah scholars across the globe should converge for harmonization of opinion to arrive at a given standard for the operation of Islamic products unification globally.